2015
DOI: 10.1007/s00429-015-1012-0
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal correlates of impulsivity and machine learning in retired professional athletes with a history of multiple concussions

Abstract: The frontotemporal cortical network is associated with behaviours such as impulsivity and aggression. The health of the uncinate fasciculus (UF) that connects the orbitofrontal cortex (OFC) with the anterior temporal lobe (ATL) may be a crucial determinant of behavioural regulation. Behavioural changes can emerge after repeated concussion and thus we used MRI to examine the UF and connected gray matter as it relates to impulsivity and aggression in retired professional football players who had sustained multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 90 publications
4
82
1
Order By: Relevance
“…An increased risk for neurodegenerative diseases in retired American football players is suggested in one study examining death certificates,43 but more research is needed. Neuroimaging studies show modest evidence of macrostructural,21 22 24 microstructural,27 functional23 32 33 and neurochemical10 17 changes in some athletes. It is important to appreciate, however, that survey studies of former collegiate20 30 31 and professional29 athletes indicate that the majority of people rate their functioning as normal and consistent with the general population.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An increased risk for neurodegenerative diseases in retired American football players is suggested in one study examining death certificates,43 but more research is needed. Neuroimaging studies show modest evidence of macrostructural,21 22 24 microstructural,27 functional23 32 33 and neurochemical10 17 changes in some athletes. It is important to appreciate, however, that survey studies of former collegiate20 30 31 and professional29 athletes indicate that the majority of people rate their functioning as normal and consistent with the general population.…”
Section: Resultsmentioning
confidence: 97%
“…Goswami and colleagues reported that football athletes with a history of concussion (n=19) had significant cortical thinning of the anterior temporal lobe and orbitofrontal cortex compared with controls (n=17) 23. Koerte and colleagues identified decreased cortical thickness in former professional soccer players (n=15) 10.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that most of these studies concern postmortem samples, there is a need for comprehensive neurobehavioural characterisation of former professional athletes from contact sports during life. Such studies have shown evidence in support of cognitive impairment above that expected with ageing alone8–10 18 (but see Casson et al )11 and, more consistently, neuropsychiatric symptoms 10 11 22 34 35. This research has included studies based on survey methods, limited batteries and no control groups.…”
Section: Discussionmentioning
confidence: 99%
“…(Of note, when these concussion variables were combined into an index with demographic variables and premorbid intellect, the index predicted cognitive outcomes). However, there have been robust findings (including class 2 evidence) between total lifetime number of concussions and risk for later-life behaviour/mood symptoms in former NFL players, especially depression[5, 7, 35], but also impulsivity[10]. Relative to cognitive impairment, behaviour/mood dysfunction in former NFL players could be more sensitive (or there could be a lower threshold) to chronic axonal damage associated with concussion[8, 36].…”
Section: Discussionmentioning
confidence: 99%
“…professional football players often experience numerous concussions throughout their athletic career[14], and recurrent concussions may place this population at risk for later-life clinical impairment. A history of recurrent concussions has been linked with structural and functional brain changes, cognitive impairment, depression, and impulsivity in former National Football League (NFL) players[510]. Exposure to repetitive head impacts (RHI; i.e., repetitive symptomatic concussions and asymptomatic subconcussive injuries) is also associated with chronic traumatic encephalopathy (CTE), a neurodegenerative disease that has been diagnosed neuropathologically in former professional American football players[1113].…”
Section: Introductionmentioning
confidence: 99%